Qaraqalpaq tili (mámleketlik til) sabaǵında mashqalalı tálimnen paydalanıwdıń bazı bir máseleleri (SCIENCE and SOCIETY, 2017)
The article deals with the issues of using educational technologies in problem teaching at the lessons in «karakalpak language», the state language. The author also describes the aims, levels and peculiarities of theoretical bases of prob- lem teaching.